Pogthefish, if you have -9= 10x + 5(x+9)-7, you cannot divide by 10 until you have isolated the 10x. Then you divide BOTH sides by 10. So, yes. You are correct. :)

For example, I am assuming you are solving for x, yes? If you are, then here are the steps to take:

Step one (multiply 5(x+9)) so that you get:

-9=10x + 5x+45 - 7

Step two (add up the numbers and add up the numbers with x):

-47 = 15x (I passed all the numbers to the left side of the equal sign)

Step three (divide BOTH sides by 15):

-47/15 = 15x/15

Step four (simplify):

-47/15 = x (15/15 becomes 1) :)

I hope this helps! Let me know if you have any questions.